Is serum phosphorous level an early indicator of post-operative hypocalcemia after total thyroidectomy? A prospective analysis - Thachil, Antony P.; Joseph, Carbin S.; David, Sandeep Kumar S. (International Surgery Journal, 2021)
Background: Total thyroidectomy is a commonly performed surgery. Postoperative hypocalcemia is a worrisome complication which can be treated if recognized early. We analysed serum phosphorous as a potential marker of postoperative hypocalcemia. Methods: The study was a cross-sectional study done in our tertiary care hospital. We analysed the serum phosphorous levels of 50 patients who underwent total thyroidectomy at our institution. The incidence of hypocalcemia was documented and analysed with respect to serum phosphorous. Results: In the study, 18 (36%) had hypocalcaemia on third postoperative day and 32 (64%) had no hypocalcaemia. There was no relation between post thyroidectomy day one serum phosphorus value and post-thyroidectomy day three serum calcium value (p=0.709). Conclusions: The study did not find any statistically significant association between serum phosphorous and post-thyroidectomy serum calcium levels.